Effect of Different Protein and Protein-Energy Ratio in Diet on Growth of Common Carp (Cyprinus carpio) Fingerling - Setiawati, M.; Sutajaya, R.; Suprayudi, M. Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
Aquaculture activity including culture of common carp (Cyprinus carpio) is now facing on high price of feed. Feed cost can reach more than 50% of production cost so that increase in feed price decreases in farmer benefit. Toward increasing in benefit, it needs efficiency on production cost. This can be achieved by using a diet containing suitable protein and protein-energy ratio for the need of fish cultured. Diet containing different protein levels (28% and 31%) and protein-energy ratios (8 and 10), and a commercial feed as a control were compared to determine protein content and protein-energy ratio suitable for common carp fingerlings. The results showed that food efficiency was differed among the treatments, while relative growth rate was similar. Diet containing protein of 31.15% with protein-energy ratio of 7.81, and protein of 28.08% with protein-energy ratio of 9.12 were resulting higher food efficiency compared to that of diet containing 31.15% protein with 7.81 protein-energy ratio and 28.27% protein with 8.28 protein-energy ratio. Keywords: common carp, Cyprinus carpio, protein-energy ratio, food efficiency ABSTRAK Kegiatan budidaya ikan termasuk ikan mas (Cyprinus carpio) saat ini dihadapkan pada kenyataan mahalnya harga pakan buatan. Kebutuhan biaya pakan dalam proses produksi mencapai lebih dari 50% sehingga menurunkan tingkat keuntungannya. Untuk meningkatkan keuntungan, diperlukan efisiensi biaya produksi yang salah satunya dengan memproduksi pakan yang mengandung kadar protein dan rasio protein terhadap energi pakan yang sesuai dengan kebutuhan ikan. Pakan dengan kadar protein (28 and 31%) dan rasio protein-energi (8 dan 10) yang berbeda diuji untuk mengetahui kandungan protein dan rasio protein-energi yang sesuai untuk fingerling ikan mas. Hasil penelitian menunjukkan bahwa fingerling ikan mas yang yang diberi pakan dengan kadar protein dan rasio protein energi yang berbeda menghasilkan tingkat efisiensi pakan yang berbeda, namun tidak mempengaruhi tingkat pertumbuhan relatifnya. Pakan dengan kadar protein 31,15% dengan rasio protein energi 7,81 dan kadar protein 28,08% dengan rasio protein energi 9,12 menghasilkan nilai efisiensi pakan yang lebih baik daripada pakan yang mengandung kadar protein 31,15% dengan rasio protein energi 7,81 dan kadar protein 28,27% dengan rasio protein energi 8,28. Kata kunci: ikan mas, Cyprinus carpio, rasio energi protein, efisiensi pakan